The Intelligent Control System of Traffic Light Based on Fog Computing. Issue 6 (1st November 2018) - Wu, Qiong; He, Fanfan; Fan, Xiumei
Abstract : The continuous increase of city motors with the improvement of society has introduced extraordinary demanding situations for the traffic situation of the town. Intelligent traffic has proposed a diversity of solutions to relieve urban traffic accidents and congestion and other troubles. It cannot regulate the cycle of traffic light in real time in keeping with the occurring traffic flux which additionally, may produce the traffic jam to result in the increase for the range of automobiles and the longer of passage time. In purpose to surmount the shortcomings of traditional traffic light control, this paper is presenting a form of intelligent control system for traffic light founding on fog computing. It calculates and shares the traffic flux situation at the intersection and the surrounding intersection through fog computing platform. Regarding the traffic flow at the intersection and the traffic flow at the surrounding intersection as the parameters, the intelligent control algorithm of traffic light is designed for achieving mutual coordination and mutual influence between different intersections, so that the traffic efficiency of each intersection is improved and the traffic flow of the entire transport network is alleviated. The simulation results showed this intelligent control system progress the traffic efficiency of every intersection and relieve the traffic flow of the whole transport network.